Implementasi Pembelajaran Mendalam dengan Praktik Pedagogis STEAM Terintegrasi Design Thinking untuk Meningkatkan Berpikir Kritis Siswa Sekolah Dasar - Herianingtyas, Nur Luthfi Rizqa; Dewi, Rosbanon; Latip, Asep Ediana; Muyassaroh, Izzah (DPPM Universitas Pelita Bangsa, 2025)
Critical Thinking is a key component of the graduate profile and poses a significant challenge in learning, including in elementary education. In this study, deep learning can encourage students to discover the meaning of what they learn, engage them in analyzing information, making connections between ideas or information, and solve problems. With STEAM pedagogical practices integrated with Design Thinking, students can engage in three deep learning experiences: understanding, applying, and reflecting. Quantitative data revealed that 164 fifth-grade elementary school students were homogeneously divided into two classes: a control class and an experimental class. A significant value of 0.000 <0.05 was obtained, with an n-gain of 0.63, categorized as moderate. STEAM integrated with Design Thinking, implemented as a pedagogical practice for deep learning, provides students with the opportunity to analyze needs, process and evaluate information, and develop ideas based on considerations that have gone through an iterative thinking process. The application of STEAM integrated with Design Thinking in deep learning encourages students to apply knowledge to new, real-world contexts through multidisciplinary approaches to build in-depth understanding.Keyword:Deep Learning, STEAM, Design Thinking, Critical Thinking